Predictive Control with On-Off actuators of Partially Fading Memory Systems. Issue 1 (July 2017) - Salvador, J.R.; Alamo, T.; Ramirez, D.R.; de la Peña, D. Muñoz
Abstract: This paper presents a new algorithm for the predictive control of systems with on-off actuators that it is tailored for systems in which part of the state vector depends only slightly on past values of the control signal beyond a certain t — L time instant. An example of this is a system with both slow and fast stable dynamics, where the fast ones vanishes after a certain time while the slow dynamics are still influencing the transient state. The algorithm is based on an iterative procedure that constructs a set of candidate solutions to the predictive control problem. The size of the candidate solutions set is reduced from 2 N to a user specified value M that can be set accordingly to the computing capabilities of the machine in which the algorithm is to be implemented. The algorithm considers nonlinear systems and although the solution is suboptimal, the approximation error is small in practice and reduces with higher M values. The results are illustrated with a simulated example.